Optimalisasi Handover Keperawatan di Ruang Rawat Inap Rumah Sakit Banda Aceh - Rachmah; Hajjul Kamil; Rosa Galica Gita Gressia; Muhammad Yusuf (CV. CENDIKIA JENIUS INDONESIA, 2025)
Nursing handover is the process of transferring responsibility and accountability among nurses in the provision of patient care in hospitals. Effective handover can reduce incident rates and improve patient safety. This study aimed to optimize nursing handover practices in inpatient wards. The method involved three stages: preparation (identifying issues and planning solutions), implementation (socializing handover procedures during shift changes, guiding the use of digital handover observation forms), and evaluation (assessing handover effectiveness). After the intervention, 88% of nursing handovers in the inpatient ward were carried out properly. It is concluded that regular socialization, strengthened supervision by head nurse or team leaders, reinforced team commitment, and balanced staffing considering education, work experience, and career level (Clinical Nurse I, II, and III) are necessary to sustain effective nursing handovers.